SALMONELLOSIS ASSOCIATED WITH WHALE MEAT IN AN ESKIMO COMMUNITY: SEROLOGIC AND BACTERIOLOGIC METHODS AS ADJUNCTS TO AN EPIDEMIOLOGIC INVESTIGATION - BENDER, THOMAS R.; JONES, T. STEPHEN; DEWITT, WALLIS E.; KAPLAN, GARY J.; SASLOW, ARNOLD R.; NEVIUS, S. EDWARD; CLARK, PAUL S.; GANGAROSA, EUGENE J. (Oxford University Press, 1972)
Bender, T. R. (CDC, 225 Eagle St., Anchorage, Alaska 99501), T. S. Jones, W. E. DeWitt, G. J. Kaplan, A. R. Saslow, S. E. Nevius, P. S. Clark and E. J. Gangarosa. Salmonellosis associated with whale meat in an Eskimo community. Serologic and bacteriologic methods as adjuncts to an epidemiologic investigation. Am J Epidemiol 96: 153–160, 1972.—In August 1969, an outbreak of Salmonella enteritidis gastroenteritis occurred in Tununak, Alaska, a small Eskimo village on the Bering Sea. Illness histories obtained from all 265 villagers revealed that 105 persons had symptoms compatible with salmonellosis for an overall attack rate of 40%. Symptoms consisted of fever, chills, nausea, vomiting, cramps, and diarrhea. Of the 99 persons who ate whale meat, 93( 94%) became ill. S. enteritidis was cultured from samples of the meat. Rectal swabs randomly collected from 135 persons were positive for S. enteritidis in 65 (48%) of the cases. Of the 17 villagers hospitalized, all had positive stools and three had positive blood cultures. A comparative study of three stool transport media one month after the start of the epidemic yielded positive isolations as follows: Hajna's (12%), Cary-Blair (17%), and tetrathionate (18%). A bacterial agglutination test was particularly useful in the retrospective evaluation of the epidemic and fourfold rises in antibody titer correlated well with clinical and bacteriologic findings.